Дом слепых: [роман] / Марина Ахмедова ; читает - А. Корсаков - Ахмедова Марина Магомеднебиевна (Национальная библиотека Удмуртской Республики, 2022)
Экземпляры: БС (20230306) / Инвентарный номер: МН2776 / Сис.шифр: 84(2) / Авт.знак: А 95 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4